Hubungan Berat Badan dengan Kejadian Infertilitas pada Wanita Usia Subur di Wilayah Kerja Puskesmas Walenrang - Lindriani Lindriani; Hertiana Hertiana (Journal of Pharmaceutical and Health Research, 2022)
The research was conducted in June 2021 at Work Area of Walenrang Health Center Kab. Palopo Year 2021. This type of research is an observational method with Cross Sectional Study approach. The population in this study were all fertile couples in the working area of Walenrang Health Center Kab. Palopo Year 2021 obtained sample of 56 people with purposive sampling technique The results showed that from 56 people who used as sample, infertility was 38 people (67,9%) and infertility did not have 18 people (32,1%). The results showed that of 56 people who used as sample, mother with obesity weight counted 37 people (66,1%) and non obesitas counted 19 people (33,9%). The results showed that there was a relationship between weight and incidence of infertility. The need for information through counseling given to couples of childbearing age about the occurrence of infertilisas and reproductive tests conducted on couples of childbearing age who have no children.